Determinants of Firm Financial Performance: A Panel Data Analysis of Macroeconomic Stability and Market Factors in LQ45 Companies in Indonesia - Mohammad Sofyan; Fatchur Rochman; Indah Purnama Sari Mardjuni; Vicky Oktavia; Mochamad Ramza Rapier Gussa (Greenation International Journal of Economics and Accounting, 2026)
This study aims to examine the factors affecting the financial performance of companies included in the LQ45 index on the Indonesia Stock Exchange by integrating macroeconomic stability and market-based indicators. Financial performance is measured by return on equity, while the independent variables include inflation, exchange rate, price-to-book value, dividend yield, and firm size. This study employs a quantitative approach using panel data from 37 companies over the period 2021 to 2025. The data are analyzed using panel regression with model selection conducted through Chow test, Lagrange Multiplier test, and Hausman test. The results indicate that the fixed effect model is the most appropriate model. Partially, price-to-book value, dividend yield, and firm size have a positive and significant effect on financial performance, while the exchange rate has a negative and significant effect. Inflation does not have a significant effect on financial performance. These findings indicate that firm-specific factors play a more dominant role than macroeconomic variables in determining financial performance. This study contributes to financial literature in emerging markets and provides insights for investors and policymakers in decision making.